21.4L: Late‐News Paper: Recent Developments of Carbon Nanotube Enabled Vertical Organic Light Emitting Transistors for OLED Displays. Issue 1 (1st July 2013) - Liu, Bo; McCarthy, Mitchell A.; Iheanacho, Bright; Wong, William S.; Rinzler, Andrew G.
Abstract A new architecture light emitting transistor combining the drive transistor, storage capacitor and light emitter into a single device promises to greatly reduce AMOLED manufacturing costs by dramatically reducing the backplane circuit complexity. Here we demonstrate device operation at 60 Hz using only a switching transistor and show remarkable stability under bias stress, despite use of an organic channel.